Influence of the Calcium Carbonate Shell of Coccolithophores on Ingestion and Growth of a Dinoflagellate Predator - Haunost, Mathias; Riebesell, Ulf; D’Amore, Francesco; Kelting, Ole; Bach, Lennart T. (Frontiers in Marine Science, 2021)
Coccolithophores are an important group of ~200 marine phytoplankton species which cover themselves with a calcium carbonate shell called “coccosphere”. Coccolithophores are ecologically and biogeochemically important but the reason why they calcify remains elusive. One key function may be that the coccosphere offers protection against microzooplankton predation, which is one of the main causes of phytoplankton death in the ocean. Here, we investigated the effect of the coccosphere on ingestion and growth of the heterotrophic dinoflagellate Oxyrrhis marina. Calcified and decalcified cells of the coccolithophore species Emiliania huxleyi, Pleurochrysis carterae, and Gephyrocapsa oceanica were offered separately to the predator as well as in an initial ~1:1 mixture. The decrease of the prey concentrations and predator abundances were monitored over a period of 48-72 hours. We found that O. marina did not actively select against calcified cells, but rather showed a size selective feeding behavior. Thus, the coccosphere does not provide a direct protection against grazing by O. marina. However, O. marina showed slower growth when calcified coccolithophores were fed. This could be due to reduced digestion rates of calcified cells and/or increased swimming efforts when ballasted with heavy calcium carbonate. Furthermore, we show that the coccosphere reduces the ingestion capacity simply by occupying much of the intracellular space of the predator. We speculate that the slower growth of the grazer when feeding on calcified cells is of limited benefit to the coccolithophore population because other co-occurring phytoplankton species within the community that do not invest energy in the formation of a calcite shell could also benefit from the reduced growth of the predators. Altogether, these new insights constitute a step forward in our understanding of the ecological relevance of calcification in coccolithophores.